Present status of conservation and management of sea turtle in Coxs Bazar district of Bangladesh - Hossain, MA; Miah, MI; Hasan, KR; Bornali, JJ; Shahjahan, M (Bangladesh Journal of Animal Science, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">The study was conducted to know the present status of conservation and management of sea turtle in Coxs Bazar district. Data were collected by physical survey, interviewing people of the study area and from different non-government and government organizations during December 2010 to November 2011. In the present study, it was found that two species of sea turtles have been making nest in Bangladesh. Major nesting sites of turtles were St. Martin's Island, Teknaf, Bordal, Sonadia Island, Kutubdia Island, Pechardwip, Inani Beach, Moheskhali Island and Shahporirdwip. A total of 260 turtle individuals were found and the highest nesting frequency of Olive ridley (108) and Green turtles (10) were observed in February. About 21,942 hatchlings were produced and released by the hatcheries as a conservational step. Winter season was identified as nesting season for sea turtle. About 45% of the respondents thought that turtles were beneficial while other 40% of the respondents thought turtles were harmful. It was found that the nesting of sea turtles was reducing and there was lack of knowledge among the people of the study area about the importance of sea turtle conservation and management. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18493 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">131-138 <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>